Between the Countryside and the City Housing typologies for Sustainable Habitats? - Fernandes del Pino, R.; Marat-Mendes, T. (ENHR 2022, 2022)
The development of housing typologies and of public spaces has received great attention in the history of architecture. Yet, the study of the habitat as a “housing/ green space” binomial remains underexplored. This presentation aims to underline the current need to create new and sustainable housing typologies associated with specific green spaces. This theme is not new, as throughout the 19th and 20th century the search for a new productive urban landscape was already central to the work of Leberecht Migge, Adolf Loos, Ildefons Cerdá and Patrick Geddes, among many others involved in the design and planning of cities. The definition of sustainable human habitat, as well as the concerns expressed in international agendas - FAO and Habitat III - express the need for new realities for the future of cities. But what will be the architectural materialization of these desires, ambitions, and ideals? What examples in history bring us closer to the values of sustainability and self-sufficiency? And what about the present? To that extent, we analyzed three winning projects of recent public tenders, in three different urban situations in the territory of the Lisbon Metropolitan Area - Almada, Setúbal and Lisbon. Here, through surveys and bibliographical review, we hope to contribute to the building of a catalog of referential solutions for constructing housing, public and green spaces that promote a direct relationship between the countryside and the city. The development of high density/low rise solutions, different scales of productive green spaces, and new interpretations of public space could serve as a basis for the creation of new urban solutions to promote better habitats and food self-sufficiency. Thus, the problem of “housing/ green space” articulation provides a unique point on which to articulate research, architecture and policy-making for the future.